Ozone as a Safe and Environmentally Friendly Tool for the Seafood Industry. Issue 2 (17th February 2016) - Gonçalves, Alex Augusto
ABSTRACT: In recent years, increasing attention has been focused on food safety, and in particular on the intervention methods to reduce and/or eliminate human pathogens from fresh products. Many research and industrial trials are underway to validate the use of ozone in the food industry as an alternative treatment to improve food safety. Notably, when ozone is applied to food surfaces, it leaves no residues since it decomposes quickly. Chemical and physical properties of ozone, its generation, and the antimicrobial power of ozone were explained as well as many advantages of ozone uses in the seafood industry.